PENGARUH FLEXTIME TERHADAP JUMLAH PESANAN GOJEK DI KOTA BANDAR LAMPUNG - Sri Suyarti; Yakub Aprilianto (Sekolah Tinggi Ilmu Ekonomi Gentiaras, 2019)
Online transportation is public transportation that is commonly used but can be operated onlineboth for ordering and payment. Flextime is a system of regulating working hours that gives morefreedom to employees that choosing work hour according to their needs. The application of flexibleworking hours greatly facilitates the driver in doing work; with this the consumer is facilitated to useGojek facilities.Based on the calculation, the effect of flextime variable (X) on the order quantity (Y) is 40.1%,and 59.9% is influenced by other factors. The results of the T test t count> t table (8,347> 1,645) meansthat there is a flextime effect on the number of orders in Gojek Bandar Lampung.